Effects of Chard (Beta VulgarisL. Var. Cicla) on Cardiac Damage in Valproic Acid-Induced Toxicity - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK; AKBAY, TUĞBA (WILEY, 2016)
The aim of this study was to examine the effects of chard on valproic acid (VPA)-induced cardiac damage. Female Sprague-Dawley rats were grouped as control, chard given control (100mg/kg/day, by gavage), VPA (500mg/kg/day, intraperitoneally) and chard given VPA (100mg/kg/day chard by gavage, 500mg/kg/day VPA, intraperitoneally). The aqueous extracts of chard leaves were given 1h prior to administration of VPA for 7 days. Malondialdehyde (MDA), total sialic acid (SA) levels and catalase (CAT) activity significantly increased in the VPA group compared with the control group (P<0.05). Chard administration significantly decreased MDA and SA levels in the control and in the VPA groups (P<0.05). Chard administration also significantly increased CAT activities and glutathione levels both in the control and in the VPA groups (P<0.05). As a conclusion, chard consumption may prevent cardiac tissue from oxidative stress and inflammation in VPA-induced toxicity. Practical ApplicationsValproic acid (VPA) is an antiepileptic drug and has severe toxic effects in experimental animals and humans. Chard (Beta vulgarisL. var. cicla) has antioxidant, antidiabetic, antitumor and hepatoprotective effects. Its protective effects against VPA toxicity have not been fully investigated yet. According to the results of this study, chard (B.vulgarisL. var. cicla) can be used as a dietary food supplement in the epilepsy treatment. The beneficial effect of chard consumption is an important finding in a nutritional point of view as chard contains many significant bioactive constituents for a healthy diet.
Keywords: INDUCED LIVER-INJURY; OXIDATIVE STRESS; DIABETIC-RATS; EXTRACT; ANTIOXIDANT; GLUTATHIONE; CATALASE; HYPERGLYCEMIA; MECHANISM; APOPTOSIS